Greater Strength Gains after Training with Accentuated Eccentric than Traditional Isoinertial Loads in Already Strength-Trained Men - Walker, Simon; Blazevich, Anthony J.; Haff, G. Gregory; Tufano, James J.; Newton, Robert U.; Häkkinen, Keijo (Frontiers in Physiology, 2016)
As training experience increases it becomes more challenging to induce further neuromuscular adaptation. Consequently, strength-trainers seek alternative training methods in order to further increase strength and muscle mass. One method is to utilize accentuated eccentric loading, which applies a greater external load during the eccentric phase of the lift as compared to the concentric phase. Based upon this practice, the purpose of this study was to determine the effects of 10 weeks of accentuated eccentric loading versus traditional isoinertial resistance training in strength-trained men. Young (22±3 y, 177±6 cm, 76±10 kg, n = 28) strength-trained men (2.6±2.2 y experience) were allocated to concentric-eccentric resistance training in the form of accentuated eccentric load (eccentric load = concentric load + 40%) or traditional resistance training, while the control group continued their normal unsupervised training program. Both intervention groups performed three sets of 6-RM (session 1) and three sets of 10-RM (session 2) bilateral leg press and unilateral knee extension exercises per week. Maximum force production was measured by unilateral isometric (110° knee angle) and isokinetic (concentric and eccentric 30°.s-1) knee extension tests, and work capacity was measured by a knee extension repetition-to-failure test. Muscle mass was assessed using panoramic ultrasound and dual-energy x-ray absorptiometry. Surface electromyogram amplitude normalized to maximum M-wave and the twitch interpolation technique were used to examine maximal muscle activation. After training, maximum isometric torque increased significantly more in the accentuated eccentric load group than control (18±10% vs. 1±5%, p<0.01), which was accompanied by an increase in voluntary activation (3.5±5%, p<0.05). Isokinetic eccentric torque increased significantly after accentuated eccentric load training only (10±9%, p<0.05), whereas concentric torque increased equally in both the accentuated eccentric load (10±9%, p<0.01) and traditional (9±6%, p<0.01) resistance training groups; however, the increase in the accentuated eccentric load group was significantly greater (p<0.05) than control (1±7%). Knee extension repetition-to-failure improved in the accentuated eccentric load group only (28%, p<0.05). Similar increases in muscle mass occurred in both intervention groups. In summary, accentuated eccentric load training led to greater increases in maximum force production, work capacity and muscle activation, but not muscle hypertrophy, in strength-trained individuals.